Somatic gene mutation signatures predict cancer type and prognosis in multiple cancers with pan-cancer 1000 gene panel. (1st February 2020) - Wang, Hai-Long; Liu, Peng-Fei; Yue, Jie; Jiang, Wen-Hua; Cui, Yun-Long; Ren, He; Wang, Han; Zhuang, Yan; Liu, Yong; Jiang, Da; Dong, Qian; Zhang, Hui; et al.
Abstract: Most cancers are caused by somatic mutations. Some common mutations in the same cancer type can form a "signature" to specifically predict the prognosis or to distinguish it from other cancers. In this study, 710 somatic cell mutations were identified in 142 cases, including digestive, lung and urogenital cancers, and the digestive cancers were further divided into liver, stomach, intestinal, esophageal and cardia cancer. The above mutations were located in 166 genes. In addition, a group of high-frequency mutation genes with specific characteristics were screened to form predictive signatures for each cancer. Verification using TCGA suggested that the signatures could predict the stages, progression-free survival, and overall survival of digestive, intestinal, and liver cancers (P < 0.05). The validation cases further confirmed the predictive role of digestive and liver cancers signatures in diagnosis and prognosis. Overall, this study established predictive signatures for different cancer systems and their subtypes. These findings enable a better understanding in cancer genome, and contribute to the personalized diagnosis and treatment. Highlights: Targeted next-generation sequencing was performed to identify predictive signatures. The signatures could predict stage, PFS and OS of digestive, intestinal and liver cancers. Digestive and liver cancer signatures could be used for diagnosis and prognosis.